2022
DOI: 10.2196/41499
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Perceptions of Jordanians Toward Adopting and Using Telemedicine: National Cross-sectional Study

Abstract: Background Due to the upsurge of COVID-19, nations are increasingly adopting telemedicine programs in anticipation of similar crises. Similar to all nations worldwide, Jordan is implementing efforts to adopt such technologies, yet it is far from complete. Objective This study aims to assess the knowledge, attitudes, and perceptions of Jordanians toward telemedicine, to identify key factors predisposing individuals to its use or acting as barriers to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
3
4
0
Order By: Relevance
“…These positive views are consistent with studies on telepharmacy 24 , 25 and telemedicine in general. 19 , 26 Likewise, aligning with other studies on telepharmacy, 27 , 28 the study showed that protecting patients during pandemics and convenience to patients living in remote areas are other vital perceived benefits in favor of telepharmacy.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These positive views are consistent with studies on telepharmacy 24 , 25 and telemedicine in general. 19 , 26 Likewise, aligning with other studies on telepharmacy, 27 , 28 the study showed that protecting patients during pandemics and convenience to patients living in remote areas are other vital perceived benefits in favor of telepharmacy.…”
Section: Discussionsupporting
confidence: 70%
“… 18 On the same line, Jordanians showed to have favorable perceptions towards telemedicine. 19 Nonetheless, no information is available regarding the use of telepharmacy among Jordanians. This study thus aimed to investigate the perception and willingness to use telepharmacy among the general population in Jordan as well as to investigate the socioeconomic disparities in patient use of telepharmacy.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings showed that T&T population have a favourable attitude towards telemedicine as the majority are willing to try mobile based health app and are not concerned about confidentiality issues raised as a major barrier in the utilization in previous studies [35,36]. Similar findings were recorded in studies on Jordanian [30] and Chinese populations [32]. A positive attitude is essential for a new technology to be adopted and used by the population, therefore there is a need to address this barrier.…”
Section: Discussionsupporting
confidence: 88%
“…Another notable finding is the infrequent use of telemedicine recorded in the present study which is consistent with findings from other developing countries [9,29,30], despite reports of surge in the use of telemedicine recorded in some developed countries [31,32]. This trend aligns with the poor awareness observed in our study and could be linked to ineffective adoption strategies.…”
Section: Awareness Of Telemedicinesupporting
confidence: 92%
See 1 more Smart Citation